Loop electrosurgical excision procedure: A Review - I Nyoman Bayu Mahendra; William Alexander Setiawan (The Indonesian Society of Perinatology, South Jakarta, Indonesia, 2023)
LEEP is a one-of-a-kind outpatient procedure for diagnosing and treating dysplastic cervical lesions. Loop diathermy treatment, loop excision of the transformation zone (LETZ), and large loop excision of the transformation zone (LLETZ) are other names. This approach yields high-quality cytologic specimens and has no negative effects on reproductive function. It also can be used to treat cervical cancer by replacing cryotherapy or laser. LEEP can be used to bypass the entire transformation zone. This is done with the help of a high-frequency, low-current electric generator and a stainless-steel loop. The LEEP procedure has a similar complication rate to cryotherapy. Bleeding is the most common complication. In addition, there may be inadequate lesion removal and cervical stenosis. LEEP has several advantages over other treatments, including removing aberrant tissue that allows cytologic examination, cheap cost, simplicity of acquiring important skills, and the potential to treat lesions with fewer visits. Patients are pleased with the surgery. LEEP is anticipated to be widely used by family physicians.